UiTM Smart Attendance Access Control System: article / Zaharah Hairuzi - Hairuzi, Zaharah (2010)
Traditional attendance recording system are still being used in most educational institutions. The traditional attendance recording method involves the distribution of attendance sheets, which are signed by students. This method of recording attendance wastes time, as well as disrupting the student’s attention in class. Furthermore, the lecturers need to check the record and calculate the attendance manually. Consequently, this influences the quality of teaching system. UiTM Smart Attendance Access Control System is proposed as a solution to this problem. This system uses Radio Frequency Identification (RFID) to access the recording attendance system which is the easier, faster and in an efficient way. The attendance will be captured immediately once the students place their ID card on the reader and the system is automated calculation of the attendance. Minimum requirements for UiTM students to qualify to seat in examination is 80%, hence the system will view the status of the students for their eligibility. The system was developed using the PIC16F877A microcontroller by Microchip and integrated with the computer through RS232 or Universal Serial Bus (USB) port. Attendance is stored in a Microsoft Access database, using integration with Visual Basic 6.0 software. A prototype of the system has been successfully developed.